A Simplified Method for Simultaneous Extraction and Purification of Stevioside and Rebaudioside A from Stevia Rebaudiana Bert. Applying in Pharmaceutical - Trong Bien, Tran; Van Han, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3DO - 10.25073/2588-1132/vnumps.4383, 2022)
Abstract: Steviol glycosides from Stevia rebaudiana Bert., notably stevioside and rebaudioside A, are ingredients with many pharmaceutical applications. In which rebaudioside A has a uniform sweetness with no bitter aftertaste. A simple method for the simultaneous extraction of stevioside and rebaudioside A has been studied with basic steps including extracting medicinal herbs with water, removing impurities using lime milk, neutralizing with citric acid, purifying with water-saturated n -butanol, and crystallizing fractional to obtain stevioside and rebaudioside A. The spectral data of IR, MS, and NMR have demonstrated the product structure as stevioside and rebaudioside A. This result is a premise for further studies. Keywords: Stevia rebaudiana , pharmaceutical, stevioside, rebaudioside A.